b. \(\dfrac{8^2.6^3}{9^2.16^2}\)
c. \(\dfrac{\left(0,15\right)^4}{\left(0,5\right)^5}\)
d. \(\left(\dfrac{3}{4}\right)^3\). \(\left(\dfrac{16}{9}\right)^3\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{5^6.25^3}{25}=\dfrac{5^6.5^6}{5^2}=5^{6+6-2}=5^{10}\)
\(\dfrac{5^6.25^3}{25}=\dfrac{5^6.\left(5^2\right)^3}{5^2}=\dfrac{5^6.5^6}{5^2}=\dfrac{5^{12}}{5^2}=5^{12-2}=5^{10}\)
\(a,\widehat{aOn}+\widehat{mOn}+\widehat{mOb}=180^o\left(kề.bù\right)\\ \Leftrightarrow70^o+\widehat{mOn}+40^o=180^o\\ Vậy:\widehat{mOn}=180^o-\left(70^o+40^o\right)=70^o\\ b,Vì:\widehat{aOn}=\widehat{mOn}\\ Mà.tia.On.nằm.giữa.2.tia.Oa.và.Om.nên:\\ On.là.tia.phân.giác.góc.\widehat{aOm}\)
\(\dfrac{1}{4}-\left(2x+\dfrac{1}{2}\right)^2=0\)
\(\left(2x+\dfrac{1}{2}\right)^2=\dfrac{1}{4}\)
=> \(\left(2x+\dfrac{1}{2}\right)^2=\left(\pm\dfrac{1}{2}\right)^2\)
=> \(2x+\dfrac{1}{2}=\pm\dfrac{1}{2}\)
TH1:
\(2x+\dfrac{1}{2}=\dfrac{1}{2}\)
\(2x=\dfrac{1}{2}-\dfrac{1}{2}=0\)
\(x=0\)
TH2:
\(2x+\dfrac{1}{2}=-\dfrac{1}{2}\)
\(2x=-\dfrac{1}{2}-\dfrac{1}{2}\)
\(2x=-1\)
\(x=\dfrac{-1}{2}\)
Vậy \(x\in\left\{0;\dfrac{-1}{2}\right\}\)
a) Số hạng thứ 20 (n=20) là
\(\left(20-1\right).4=76\)
\(A=1-5+9-13+17-21+...+76\)
\(A=\left(-4\right)+\left(-4\right)+\left(-4\right)+...+\left(-4\right)\)
\(A=\left(-4\right).38=-152\)
b) Số hạng thứ n là:
\(\left(n-1\right).4\)
\(\)\(A=1-5+9-13+17-21+...+\left(n-1\right).4\)
\(A=\left(-4\right)+\left(-4\right)+\left(-4\right)+...+\left(-4\right)\) ((n-1).2 số -4)
\(A=\left(-4\right).\left(n-1\right).2=-8\left(n-1\right)\)
\(\dfrac{5}{7}:x+1=\dfrac{-15}{30}\)
\(\dfrac{5}{7}:x=\dfrac{-15}{30}-1\)
\(\dfrac{5}{7}:x=\dfrac{-45}{30}\)
\(x=\dfrac{5}{7}:\dfrac{-45}{30}\)
\(x=\dfrac{-10}{21}\)
\(\dfrac{5}{7}:x+1=-\dfrac{15}{30}\)
\(\Rightarrow\dfrac{5}{7}:x+1=-\dfrac{1}{2}\)
\(\Rightarrow\dfrac{5}{7}:x=-\dfrac{1}{2}-1\)
\(\Rightarrow\dfrac{5}{7}:x=-\dfrac{3}{2}\)
\(\Rightarrow x=\dfrac{5}{7}:-\dfrac{3}{2}\)
\(\Rightarrow x=-\dfrac{10}{21}\)
\(\left(x-\dfrac{1}{2}\right):\dfrac{9}{11}=\dfrac{11}{3}\)
\(\Rightarrow x-\dfrac{1}{2}=\dfrac{11}{3}\cdot\dfrac{9}{11}\)
\(\Rightarrow x-\dfrac{1}{2}=\dfrac{9}{3}\)
\(\Rightarrow x-\dfrac{1}{2}=3\)
\(\Rightarrow x=3+\dfrac{1}{2}\)
\(\Rightarrow x=\dfrac{7}{2}\)
\(\left(x-\dfrac{1}{2}\right):\dfrac{9}{11}=\dfrac{11}{3}\\ \\ \\ \Rightarrow x-\dfrac{1}{2}=\dfrac{11}{3}\cdot\dfrac{9}{11}=\dfrac{9}{3}=3\\ \\ \\ \Rightarrow x=3+\dfrac{1}{2}=3\dfrac{1}{2}\)
\(\dfrac{8^2.6^3}{9^2.16^2}=\dfrac{\left(2^3\right)^2.2^3.3^3}{\left(3^2\right)^2.\left(2^4\right)^2}=\dfrac{2^{3.2+3}.3^3}{3^4.2^8}=\dfrac{3^3.2^8.2}{3.3^3.2^8}=\dfrac{2}{3}\\ ---\\ \dfrac{\left(0,15\right)^4}{\left(0,5\right)^5}=\left(\dfrac{0,15}{0,5}\right)^4.\dfrac{1}{0,5}=\left(\dfrac{3}{10}\right)^4.2=\dfrac{81}{10000}.2=\dfrac{81}{5000}\\ ---\\ d,\left(\dfrac{3}{4}\right)^3.\left(\dfrac{16}{9}\right)^3=\left(\dfrac{3}{4}.\dfrac{16}{9}\right)^3=\left(\dfrac{48}{32}\right)^3=\left(\dfrac{3}{2}\right)^3=\dfrac{27}{8}\)
b) \(\dfrac{8^2.6^3}{9^2.16^2}=\dfrac{2^6.2^3.3^3}{3^4.2^8}=\dfrac{2^9.3^3}{3^4.2^8}=\dfrac{2}{3}\)
c) \(\dfrac{\left(0,15\right)^4}{\left(0,5\right)^5}=\dfrac{\left(0,5\right)^4.\left(0,3\right)^4}{\left(0,5\right)^5}=\dfrac{0,3^4}{0,5}\)
d) \(\left(\dfrac{3}{4}\right)^3.\left(\dfrac{16}{9}\right)^3=\dfrac{3^3}{4^3}.\dfrac{4^6}{3^6}=\dfrac{4^3}{3^3}=\left(\dfrac{4}{3}\right)^3\)